A first report on the crystal structure of hydrazine based solid solution precursor, Mn0.61Zn0.39(OOCCHNNH2)2(H2O)2 - R. Pradeep; B. Subramani; L. Ragunath; B.N. Sivasankar (Journal of Saudi Chemical Society)
A novel mixed metal complex, [Mn0.61Zn0.39(OOCCHNNH2)2(H2O)2] has been synthesized and characterized by hydrazine and metal analyses, CHN analyses, infrared spectra, simultaneous TG-DTA and single crystal X-ray diffraction studies. The structure of the complex has been determined by X-ray single crystal study which clearly reveals that the octahedral site is occupied by two metal ions (viz., Mn and Zn) around which two hydrazoneglyoxylate ligands (OOCCHNNH2) coordinate in a bidentate chelating fashion. Two water molecules occupy the remaining two other sites of a slightly distorted octahedron with C2 axis of symmetry. The infrared spectrum reveals the monodentate coordination behavior of carboxylate ions and coordination of water molecules. The simultaneous TG-DTA traces are in accordance with the formation of mixed metal oxide (spinel oxide) as an end product. The high resolution scanning electron microscopy (HRSEM) images show the presence of irregularly shaped agglomerated particles of sub-micron size. The zeta potential value for mixed metal oxide is −33.1 mV, which indicates the stability of the oxide.